Functional Properties of Cacao (Theobroma cacao L.) Leaves Kombucha - Beatrice Lokita; Yuniwaty Halim (University of Sultan Ageng Tirtayasa, 2026)
Indonesia is one of the world's largest cacao producers, generating substantial amounts of cacao leaf biomass through routine pruning practices. These leaves are often discarded despite their potential as a valuable source of bioactive compounds. Previous studies have reported that cacao leaves (Theobroma cacao L.) contain high levels of phenolic compounds and exhibit considerable antioxidant activity, highlighting their potential for further utilization. This study investigated the effect of cacao leaf processing methods and kombucha fermentation conditions on the antioxidant properties and sensory characteristics of cacao leaf kombucha. Cacao leaves were processed using either non-fermentation or full fermentation prior to tea preparation. The results showed that non-fermented cacao leaves exhibited significantly higher antioxidant activity, with an IC₅₀ value of 23,267.75 ± 2,117.60 ppm, and were therefore selected for kombucha production. Kombucha was prepared using different ratios of cacao leaf tea to starter tea (40:60, 50:50, and 60:40) and fermented for 7, 10, and 13 days. The highest antioxidant activity, total phenolic content, and total flavonoid content were obtained from kombucha prepared with a 40:60 ratio and fermented for 10 days. Sensory evaluation using a hedonic test yielded an overall acceptability score of 5.11 ± 1.45, indicating that the panelists slightly liked the product. These findings demonstrate that cacao leaves have promising potential as a raw material for kombucha production with enhanced functional properties.